Human liver microsomes study on the inhibitory effect of plantainoside D on the activity of cytochrome P450 activity - Jin Zhou; Xian Qian; Yanqing Zhou; Shili Xiong; Shuxia Ji; Ying Wang; Ping Zhao (BMC, 2022)
Abstract Background Plantainoside D is widely existed in the herbs and possesses various pharmacological activities, making it possible to co-administrate with other herbs. Its effect on cytochrome P450 enzymes (P450) is a risk factor for inducing adverse drug-drug interactions. To assess the effect of plantainoside D on the activity of major P450 isoenzymes in human liver microsomes. Methods The Cocktail method was conducted in human liver microsomes in the presence of probe substrates. The activity of P450 isoenzymes was evaluated by the production of corresponding metabolites. The concentration-dependent and time-dependent inhibition assays were performed in the presence of 0, 2.5, 5, 10, 25, 50, and 100 μM plantainoside D to characterize the inhibitory effect of plantainoside D. Results Significant inhibition was observed in the activity of CYP1A2, 2D6, and 3A, which was concentration-dependent with the IC50 values of 12.83, 8.39, and 14.66 μM, respectively. The non-competitive manner and competitive manner were observed in the CYP3A inhibition (Ki = 7.16 μM) and CYP1A2 (Ki = 6.26 μM) and 2D6 inhibition (Ki = 4.54 μM), respectively. Additionally, the inhibition of CYP3A was found to be time-dependent with the KI of 1.28 μM−1 and K inact of 0.039 min−1. Conclusions Weak inhibitory effects of plantainoside D on the activity of CYP1A2, 2D6, and 3A were revealed in vitro, implying its potential of inducing interactions with CYP1A2-, 2D6-, and 3A-metabolized drugs. Although further in vivo validations are needed, the feasibility of the Cocktail method in evaluating P450 activity has been verified.